OCCUPATIONAL STRESS AND JOB PERFORMANCE - Kousar,Sumaira; Dogar, Imtiaz Ahmad; Ghazal, Saima; Khattak, Idrees (Journal of Pakistan Psychiatric Society, 2006)
Objective: The present study was conducted to assess the levels of stress among five different depart- ments of a Multinational Corporation and the effect of stress on employee performance. Design: Cross sectional Survey. Place and duration of study: Workplace of a multinational organization factory located near Faisalabad from March 2005 to July 2005. Subjects and Methods: Sample consisted of 65 employees working in 5 different Departments of a multinational organization. Occupational stress scale (OSS) consisting of nine factors contributing to stress was used to assess stress level of workers and its effect on performance was measured by the job performance rating scale. One-way Analysis of Variance (ANOVA) was applied to see the difference in stress level of workers among five different departments and correlation analysis was done to see the relationship of stress and performance. Results: Results showed that employees in the Human Resource, Productions, Engineering & Refrig- eration, Stores and Electrical & Instrument Departments had moderate levels of stress due to work overload, co-workers and repetitive work. However there was significant negative correlation between workload and job performance (-0.286; p<0.05). But there was no significant relationship between level of overall stress and job performance. Conclusion: It was concluded that there was moderate level of stress with no significant difference in different departments however no affect of stress was found on job performance. Key words: Occupational stress, Job performance, OSS.